Pengaruh Nilai Pelanggan, Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen di Sura Coffe Surabaya - Elok Kencono Murti; Nova Retnowati; Heri Kusaeri (Indonesian Journal of Management Science, 2023)
This study aims to determine the effect of customer value, service quality, and price on customer satisfaction at Sura Coffee Surabaya. The sampling technique was carried out by the Random Sampling method. Data was collected by means of online questionnaires using google documents and 99 respondents were taken. Statistical method using Validity and Reliability test, Multiple Linear Regression Analysis, with hypothesis testing F statistic test and t statistic test. The results of this study indicate the F test that customer value, service quality, and price simultaneously and significantly affect consumer satisfaction. By t-test, the variables of Customer Value, Service Quality, and Price partially and significantly affect Sura Coffee Surabaya's Consumer Satisfaction. The results of the study Dominantly Among Customer Value, Service Quality, and Price, the dominant influence on Sura Coffee Surabaya Consumer Satisfaction is Customer Value.